Evaluasi Penggunaan Pada Website Dinas Pendidikan dan Kebudayaan Kabupaten Tebo Menggunakan Usability Testing - Fingki Lamhot Pasaribu; Marshal` Koko Anand; Naldi Irfan; Yovi Pratama (TIN: Terapan Informatika Nusantara, 2023)
The Tebo Regency Education and Culture Office is one of the service agencies in Jambi Province. his task is to assist the Regent in carrying out government affairs in the field of educational development, non-formal education and basic education, and cultural processing. on the website Dinasdikbud.tebokab.go.id there has been a significant reduction in visitors of fifteen thousand. Based on these problems, this research was made to analyze the level of satisfaction using the website using the USABILITY TESTING method. With 6 variables namely: Learnability, Efficiency, Memorability, Information Quality, Error, and Satisfaction. This study obtained respondents as many as 100 respondents. The processing of this research data used IBM SPSS Statistics 26 ver 2 software. The results of this study showed that of the 5 variables of USABILITY TESTING, 2 variables namely Efficiency and Memorability did not have a positive effect, only 3 namely Learnability, Information Quality, and Error which significantly affected Satisfaction using the Tebo District Education and Culture Office website